Causal analysis between liquidity and profitability: Is there any difference between public and private commercial banks in Bangladesh? - Qamarullah Bin Tariq Islam (Journal of Banking and Financial Economics (JBFE), 2020)
This paper analyzes the causal relationship between liquidity and profitability for public and private commercial banks in Bangladesh. The augmented Dickey-Fuller test of stationarity is carried out first. As they are found to be integrated of the same order, the Engle-Granger test of cointegration is applied. Finally, the Granger causality test is applied to check if there is any causal relationship between liquidity and profitability for public and private commercial banks in Bangladesh from 2001 to 2019. Another aim of the paper is to see if there is any difference in the causal relationship between these two bank typologies. The results show that there is unidirectional causality from profitability to liquidity for public banks while no causal relationship is evident for private commercial banks in Bangladesh. The findings further confirm that different bank typologies behave differently in Bangladesh and hence policy makers should keep this in mind during policy formulation.
Keywords: C32; E58; G21; 330; bank liquidity; profitability; causality; public and private banks; Bangladesh